The Role of Parental Psychological Control and Warmth in College Students' Relational Aggression and Friendship Quality. Issue 1 (February 2018) - Baumgardner, Megan; Boyatzis, Chris J.
This study investigated the role of perceived parental psychological control and warmth in college students' friendship quality and use of relational aggression with peers. College students ( N = 237) completed self-report measures assessing their relational aggression, friendship quality, and parents' perceived use of psychological control and warmth. As predicted, college students' relational aggression partially mediated the relation between perceived parental psychological control and friendship quality. Moderation analyses indicated that perceived parental warmth exacerbated the negative effects of perceived parental psychological control on college students' relational aggression and friendship quality. Thus, perceived parental psychological control is associated with students' elevated relational aggression and poor friendship quality, especially when parents are viewed as warm as accepting.